Analysis of Land Use Change on Environmental Degradation: A Literature Review in Urban Areas - Latue, Theochrasia; Latue, Philia C (PT. Riset Press International, 2024)
This research presents a literature review on the analysis of land use change in urban areas and its impact on environmental degradation. Rapid and uncontrolled land use change in urban areas has resulted in the conversion of green land into residential, commercial, and industrial zones, with impacts such as urban heat island, air and water pollution, and loss of natural habitats. This research used a descriptive qualitative approach. The type of research used was a literature study. The results of this study show that it is important to have an in-depth understanding of land use change trends, their impacts on the environment, and their implications for urban sustainability. The results highlight the need for wise regional planning, sustainable natural resource management, and policies that consider environmental aspects to address the challenges of environmental degradation in urban areas.